Facile and Scalable Fabrication of Transparent and High Performance Pt/Reduced Graphene Oxide Hybrid Counter Electrode for Dye-Sensitized Solar Cells - Gong, Hee Hyun; Park, So Hyun; Lee, Sang-Soo; Hong, Sung Chul (KOREAN SOC PRECISION ENG, 2014)
Platinum (Pt)-reduced graphene oxide (rGO) hybrid, prepared through a simple sequential spin coating and a concurrent thermal reduction of GO and Pt precursors, afford transparent and extraordinarily efficient counter electrode (CE) for dye sensitized solar cell (DSSC). Even with the minor amount of Pt, the hybrid CE exhibits high electrocatalytic activity, resulting in very high solar-to-electricity energy conversion efficiency (eta). The c values of the DSSCs with the hybrid CEs are even higher than that of DSSC with standard Pt based CE. Owing to the nanoscopic dimension of the rGO and Pt, the CE retains excellent transparency, which differentiates the CE from other conventional carbon based black and opaque CEs. The high catalytic behavior of the Pt-rGO hybrid CE is partly attributed to the large surface area of the hybrid CE. A synergistic combination of the rGO and Pt also imparts a low charge transfer resistance and improved redox reaction capability at the CE/electrolyte interface, as evidenced by electrochemical impedance measurements.
Keywords: WALLED CARBON NANOTUBES; PLATINUM; COMPOSITE; FILMS; EFFICIENT; NANOCOMPOSITES; SYSTEM